MOTIVASI BELAJAR SISWA DAN KETERLIBATAN SISWA DALAM PEMBELAJARAN DARING PENDIDIKAN JASMANI - Tatang Suryadin (Universitas Majalengka, 2022)
This research aims to find out students' learning motivation and student involvement in online learning of physical education to the Junior Highschool students at SMPN 1 Arjawinangun. This research is a survey study using a quantitative descriptive approach. The instruments in this study used anket, while the sampling technique was simple random sampling. With a sample number of 92 students. Analysis of the data used in this study is a quantitative descriptive analysis with percentages. The results of this study show the motivation of learning students in online learning of physical education in SMPN 1 Arjawinangun. In detail it shows the motivation for learning students in the high category with an average of 92 respondents of 94.43 (78.70%). Motivation to study students in online learning physical education which is very high thanks to 31 students (34%), high in number 60 students (65%), low in 1 student (1%) and very low in number of 0 students (0%). Whereas the results of research on student involvement in online learning of physical education in the high category, with an average of 92 respondents of 59.97 or (74.96%). Student involvement in online learning physical education which is very highly categorized by 15 students (16%), high in 75 students (82%), low in 2 students (2%) and very low in 0 students (0%).